Corporate Governance and Performance of Commercial Banks Listed at the Nairobi Securities Exchange, Kenya - Aluoch, Moses Odhiambo (European Scientific Journal, ESJ, 2023)
This study examined the relationships among corporate governance, financial characteristics, macroeconomic variables and financial performance of banking firms listed at the Nairobi Securities Exchange. The specific objectives were to establish the effect of corporate governance on performance of listed commercial banks; to determine the intervening effect of financial characteristics on the relationship between corporate governance and financial performance of banking firms; to establish the moderating effect macroeconomic variables on the relationship between corporate governance and financial performance of listed commercial banks; and to determine the joint effect of corporate governance, financial characteristics and macroeconomic variables on financial performance of listed commercial banks. This study was anchored on, agency, stewardship, resource and wealth maximization theories and positivism philosophy. The study used census approach and targeted population of 11 listed banking firms between 2006 and 2020 was incorporated. The study used panel data extracted from annual reports of the individuals firms, while macroeconomic variables data were extracted from Central Bank of Kenya and Kenya National Bureau of Statistics economic reports. This study used longitudinal descriptive research design to determine relationships amongst independent, intervening, moderating and dependent variables. The study findings indicated that corporate governance, financial characteristics and macroeconomic variables were good predictors of listed commercial banks financial performance. Financial Leverage, Interest Rates and Inflation Rates had a significant effect on Return on Assets while Corporate Governance, Investments, Liquidity and Gross Domestic Product Growth Rate were found to have insignificant effect on Return on Assets. The findings also revealed that Financial Leverage, Inflation Rates and Gross Domestic Product Growth rate had a significant effect on Tobin’s Q of listed commercial banks in Kenya. The relationship between Corporate Governance, Investments, Liquidity and Interest Rates and Tobin’s Q was found to be insignificant. The study concluded that corporate governance, financial characteristics and macroeconomic variables affect financial performance commercial banks. Listed commercial banks therefore should adhere to corporate governance guidelines both from the Central Bank of Kenya and Capital Markets Authority of Kenya for continuous sound financial performance.